A BIG DATA AND IT’S SECURITY CHALLENGE IN DIGITAL MEDIA - Vinod Khakre, Dr. Satish Agnihotri (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research work discuss about the big data and related problem. In the current generation big data play’s an important role in various data mining application. This research work discuss the various field in which apply big data application. There are many critical issues and challenges face in the big data. Big Data Duplication is one of the challenging problem between researchers. In the last decade the growth of big data exponentiation, Terabytes, Petabyte, Exabyte, Zettabyte bytes data generated in every day in a single stock market research application. In this process huge amount of decapitate data also generated in Terabytes as well as Petabytes. Similar that social media application generated large amount of duplicate information. In this research work focus on different problems and hurdles of big data and its related issues.However, encrypted information introduce new challenges for cloud information de-duplication that becomes crucial for giant information storage and process in cloud. De-duplication schemes cannot work on encrypted information. Existing solutions of encrypted information de-duplication suffer from security weakness. They cannot flexibly support information access management [13] and revocation. Therefore, few of them is pronto deployed in observe. During this paper, we propose a theme to de-duplicate encrypted information hold on in cloud supported possession challenge and proxy re-encryption. It integrates cloud information de-duplication with access management.